Pemeliharaan Ikan Sidat dengan Sistem Air Bersirkulasi - Ridwan Affandi; Tatag Budiardi; Ronny Irawan Wahju; Am Azbas Taurusman (Jurnal Ilmu Pertanian Indonesia, 2013)
Today, eel resource especially seeds in Indonesia has not been used for eel culture activities. To be able to optimally utilize the seeds that led to the production of eels for consumption needs adequate cultivation technology. This study aimed to obtain performance information of survival rate, growth rate, and feed conversion ratio to support mass production of eel consumption. The experiments were performed using aquarium of (0.8 x 0.4 x 0.4) m3 and concrete tank (1.7 x 1.7 x 1) m3with circulating water. Eel used were elver (1.2-1.5 g) and fingerlings (15-17 g). Silk worms (Tubifex) and artificial feed in the pasta form were used as feed. The results showed that the elver reared in aquarium or concrete tank with water recirculation system showed high survival rate of 78-79% and 86-96%, respectively. The specific growth rate (SGR) was good (0.6-0.8%), but the feed conversion was still high (33-21) for the elver fed with silk worms and very good (0.6-0.7) for elver fed with artificial feed. The juvenile eel reared in a concrete tank showed SR up to 85-94%, the SGR ranged from 0.8 to 1.2%, and feed conversion from 0.61 to 0.69. It can be concluded that the rearing of seed eel can be done incontainer using water recirculation system with stocking density of 3 individuals/land 1.5 kg/m3in preparing the seed to be ready tobe cultivated outdoors.